Electrolyte and lithium ion battery

By using additives such as vinyl trimethoxysilane, propane sulfonate pyridine salt and bis(trimethylsilyl)sulfate in the electrolyte of lithium-ion batteries, a high mechanical strength and flexibility SEI film and protective film are formed, which solves the problems of poor circulation performance and poor high and low temperature performance of lithium-ion batteries, and achieves a comprehensive improvement of battery performance.

CN119725752AActive Publication Date: 2025-03-28EVE ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411913716.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Lithium-ion batteries including silicon negative electrode materials in the prior art have problems such as poor circulation performance and poor high and low temperature performance.

Method used

An electrolyte is provided, which includes organic solvents, LiPF6 and specific additives, including vinyl trimethoxysilane, pyridine propane sulfonate salt and bis(trimethylsilyl)sulfate. These additives are capable of forming a SEI film with high mechanical strength and flexibility on the surface of the silicon negative electrode, and forming a protective film on the surface of the positive electrode and the negative electrode, synergistically forming a protective layer of a three-dimensional network.

Benefits of technology

By optimizing the combination of additives, the circulation performance and high and low temperature performance of lithium-ion batteries are significantly improved, the service life of the battery is extended, and the problem of PS is greatly harmful to the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207054280000091
    Figure BDA0005207054280000091
  • Figure BDA0005207054280000101
    Figure BDA0005207054280000101
Patent Text Reader

Abstract

The invention provides an electrolyte and a lithium ion battery. The electrolyte comprises an organic solvent, LiPF6 and an additive, wherein the additive comprises vinyltrimethoxysilane, pyridinium propane sulfonate and bis (trimethylsilyl) sulfate. The vinyl trimethoxy silane additive can form an organic polymer containing unsaturated bonds and a cross polymerization network containing Si-O-Si bonds on the surface of a silicon negative electrode, so that the mechanical strength and flexibility of an SEI film are improved. The pyridinium propane sulfonate and the bis (trimethylsilyl) sulfate can form a small amount of sulfur-containing compound of a positive electrode protection film, and can also form an unstable solid electrolyte passivation film on the surface of a negative electrode and a sulfur-containing compound which is easy to decompose on the surface of the positive electrode at the same time. Through the synergistic effect of the three additives, the cycle performance and high and low temperature performance of the battery are effectively improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an electrolyte and a lithium-ion battery. Background Art

[0002] Classic film-forming additives such as FEC, VC, PS, DTD, etc. occupy an important position in lithium-ion batteries. However, with the increase in the proportion of silicon doping and the continuous development of high-voltage materials, conventional additives cannot meet the needs of long-cycle and wide-temperature working environments. From the current commercial application, DTD can significantly improve the high-temperature storage and high-temperature cycle performance of the battery. It is the most effective additive among sulfate compounds, but the cost of DTD is relatively high, and its low-temperature storage requirement brings inconvenience to the transportation and storage of the electrolyte; after VC is film-formed, there are oxidation stability problems in the high-temperature and high-voltage system, which leads to a series of double decompositions. Although PS performs well in inhibiting gas production, it is easy to continuously oxidize with the positive electrode, increase the membrane impedance, and have problems such as rapid growth of internal resistance and DCR in long cycles. PS has defects such as great harm to the body and has been banned in some countries.

[0003] Negative electrode materials with high specific capacity are an important breakthrough in improving the energy density of lithium-ion batteries. Compared with graphite negative electrodes, silicon-carbon negative electrodes have obvious advantages in compaction density and specific capacity. It is difficult to significantly improve graphite negative electrode materials, and the theoretical energy density of 372mAh / g is far from the theoretical energy density of silicon negative electrode materials as high as 4200mAh / g. Suitable discharge potentials and relatively abundant reserves in nature are considered to be the most likely negative electrode materials to replace graphite.

[0004] However, there are many problems in the commercial application of single silicon in lithium-ion batteries. On the one hand, internal stress is generated in the process of lithium ion embedding and de-embedding silicon materials, which in turn causes volume expansion and damages the material structure, and may lead to the rupture of active particles, pulverization of pole pieces, and shedding of active materials. On the other hand, due to the change in silicon volume, the solid electrolyte interface film (SEI) will rupture, and the newly exposed silicon on the surface will produce a new SEI film, while continuously consuming lithium ions in the electrolyte, reducing the initial coulombic efficiency. Finally, during the cycle, due to the volume change of the electrode material, the SEI film at the silicon negative electrode interface repeatedly grows and ruptures, and the lithium source is quickly consumed. A series of problems together lead to rapid capacity decay, which greatly affects the cycle stability.

[0005] In summary, in the research and development of lithium-ion batteries with silicon negative electrode materials, selecting suitable additives and developing matching injection and formation methods are particularly critical for improving the first coulombic efficiency of lithium batteries, improving cycle stability, reducing internal resistance, and improving high and low temperature working performance. Summary of the invention

[0006] The main purpose of the present application is to provide an electrolyte and a lithium-ion battery to solve the problems of poor cycle performance and poor high and low temperature performance of lithium-ion batteries including silicon negative electrode materials in the prior art.

[0007] In order to achieve the above object, according to one aspect of the present application, an electrolyte is provided, which includes an organic solvent, LiPF 6 and additives, the additives comprising vinyltrimethoxysilane, pyridinium propanesulfonate and bis(trimethylsilyl)sulfate.

[0008] Furthermore, the mass of vinyltrimethoxysilane accounts for 0.1-5wt% of the total mass of the electrolyte, the mass of propanesulfonic acid pyridinium salt accounts for 0.1-5wt% of the total mass of the electrolyte, and the mass of bis(trimethylsilyl) sulfate accounts for 0.1-5wt% of the total mass of the electrolyte.

[0009] Furthermore, the mass ratio of vinyltrimethoxysilane, propanesulfonic acid pyridinium salt and bis(trimethylsilyl)sulfate is 0.1-3:0.1-3:0.1-3.

[0010] Furthermore, the electrolyte also includes a first auxiliary agent, which includes lithium difluorooxalatoborate and fluoroethylene carbonate, the mass of lithium difluorooxalatoborate accounts for 0.3-1wt% of the total mass of the electrolyte, and / or the mass of fluoroethylene carbonate accounts for 1-12wt% of the total mass of the electrolyte.

[0011] Furthermore, the mass ratio of the additive to the first auxiliary agent is 0.3-1:1-12.

[0012] Furthermore, the electrolyte further comprises a second auxiliary agent, the second auxiliary agent comprising C 4 H 6 N 2 and / or LiPO 2 F 2 , C 4 H 6 N 2 The mass of LiPO accounts for 0.5-1.5wt% of the total mass of the electrolyte, and / or LiPO 2 F 2 The mass of the electrolyte accounts for 0.1 to 1 wt% of the total mass of the electrolyte.

[0013] Furthermore, the organic solvent includes ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate and propyl propionate; wherein the mass ratio of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate and propyl propionate is 10-20:5-15:5-15:5-15:45-60.

[0014] Furthermore, LiPF6 The mass of the electrolyte accounts for 10-15wt% of the total mass of the electrolyte.

[0015] Furthermore, the electrolyte includes, by weight percentage, 0.1 to 3 wt % of vinyl trimethoxy silane, 0.1 to 3 wt % of propane sulfonic acid pyridinium salt, 0.1 to 3 wt % of bis (trimethylsilyl) sulfate, 10 to 15 wt % of LiPF 6 and an organic solvent; and / or, the electrolyte comprises 0.1 to 3 wt% of vinyl trimethoxy silane, 0.1 to 3 wt% of propane sulfonic acid pyridinium salt, 0.1 to 3 wt% of bis (trimethylsilyl) sulfate, 10 to 15 wt% of LiPF 6 , 0.3-1 wt% of lithium difluorooxalate borate, 1-12 wt% of fluoroethylene carbonate, 0.5-1.5 wt% of C 4 H 6 N 2 , 0.3-1wt% LiPO 2 F 2 and organic solvents.

[0016] According to another aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte is the electrolyte described above.

[0017] Applying the technical solution of the present application, the present application provides an electrolyte capable of improving the electrical performance of a lithium-ion battery including a silicon negative electrode material by optimizing the combination of additives. Specifically, the vinyltrimethoxysilane additive used in the present application can form an organic polymer containing unsaturated bonds and a cross-polymer network containing Si-O-Si bonds on the surface of the silicon negative electrode, thereby improving the mechanical strength and flexibility of the SEI film. Propane sulfonic acid pyridinium salt and bis(trimethylsilyl) sulfate can form a small amount of sulfur-containing compounds that form a positive electrode protective film, and can also be a sulfur-containing compound that is easily decomposed on the positive electrode surface while forming an unstable solid electrolyte passivation film on the negative electrode surface. It can also react with the SEI of an organic polymer containing unsaturated bonds generated by the vinyltrimethoxysilane additive, inhibiting the further decomposition of the SEI of the organic polymer, thereby modifying the SEI. Through the synergistic effect of the above three additives, a protective layer with a three-dimensional network can be formed on the cathode of the battery, providing a cross-linked protective layer respectively, forming a SEI with high electrical conductivity and high thermal stability, so that the various performances of the battery are balanced, and the cycle performance and high and low temperature performance of the battery are effectively improved, the service life of the battery is extended, and the harmful effects of PS on the body are solved. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.

[0019] As analyzed in the background technology, lithium-ion batteries including silicon negative electrode materials in the prior art have the problems of poor cycle performance and poor high and low temperature performance. To solve this problem, the present application provides an electrolyte and a lithium-ion battery.

[0020] In a typical embodiment of the present application, an electrolyte is provided, which includes an organic solvent, LiPF 6 and additives, the additives comprising vinyltrimethoxysilane, pyridinium propanesulfonate and bis(trimethylsilyl)sulfate.

[0021] The present application provides an electrolyte capable of improving the electrical performance of a lithium-ion battery including a silicon negative electrode material by optimizing the combination of additives. Specifically, the vinyl trimethoxysilane additive used in the present application can form an organic polymer containing unsaturated bonds and a cross-polymer network containing Si-O-Si bonds on the surface of the silicon negative electrode, thereby improving the mechanical strength and flexibility of the SEI film. Propane sulfonic acid pyridinium salt and bis (trimethylsilyl) sulfate can form a small amount of sulfur-containing compounds of the positive electrode protective film, and can also be a sulfur-containing compound that is easily decomposed on the positive electrode surface while forming an unstable solid electrolyte passivation film on the negative electrode surface. It can also react with the SEI of the organic polymer containing unsaturated bonds generated by the vinyl trimethoxysilane additive to inhibit the further decomposition of the SEI of the organic polymer, thereby playing a role in modifying the SEI. Through the synergistic effect of the above three additives, a protective layer with a three-dimensional network can be formed on the cathode of the battery, and a cross-linked protective layer is provided respectively to form a SEI with high conductivity and high thermal stability, so that the various performances of the battery are balanced, and the cycle performance and high and low temperature performance of the battery are effectively improved, and the service life of the battery is extended, and the influence of the presence of PS on the body is greatly harmful.

[0022] In one embodiment of the present application, the mass of the above-mentioned vinyltrimethoxysilane accounts for 0.1 to 5wt% of the total mass of the electrolyte, the mass of propanesulfonic acid pyridinium salt accounts for 0.1 to 5wt% of the total mass of the electrolyte, and the mass of bis(trimethylsilyl) sulfate accounts for 0.1 to 5wt% of the total mass of the electrolyte.

[0023] Too high or too low a concentration is not conducive to the effective formation of the required SEI film, or leads to an increase in electrolyte cost and a decrease in performance. The present application further limits the content of the additive, which is more conducive to the formation of an organic polymer containing unsaturated bonds and a cross-polymer network containing Si-O-Si bonds on the surface of the silicon negative electrode, as well as the formation of an SEI reaction of an organic polymer containing unsaturated bonds, inhibits further decomposition of the SEI of the organic polymer, and improves the mechanical strength and flexibility of the SEI film, thereby facilitating the improvement of the battery's first coulombic efficiency, improving cycle stability, reducing internal resistance, and improving high and low temperature working performance, while also helping to reduce costs.

[0024] In one embodiment of the present application, the mass ratio of the above-mentioned vinyltrimethoxysilane, propanesulfonic acid pyridinium salt and bis(trimethylsilyl) sulfate is 0.1-3:0.1-3:0.1-3.

[0025] By controlling the ratio between the above three additives within the above range, a protective layer with a three-dimensional network can be formed on the cathode of the battery through the synergistic effect of the above three additives, which plays the role of a cross-linked protective layer, thereby facilitating the uniform formation of the SEI film, improving its mechanical strength and flexibility, reducing the internal resistance growth of the battery during the cycle and the rupture of the SEI film, thereby extending the battery life and improving the battery safety.

[0026] In one embodiment of the present application, the above-mentioned electrolyte also includes a first auxiliary agent, which includes lithium difluorooxalatoborate and fluoroethylene carbonate, the mass of lithium difluorooxalatoborate accounts for 0.3-1wt% of the total mass of the electrolyte, and / or the mass of fluoroethylene carbonate accounts for 1-12wt% of the total mass of the electrolyte.

[0027] Lithium difluorooxalatoborate and fluoroethylene carbonate can enhance the stability of the SEI film and the embedding / de-embedding efficiency of lithium ions in the electrode material. By controlling the content of lithium difluorooxalatoborate and fluoroethylene carbonate within the above range, it is beneficial to improve the first coulombic efficiency of the battery, enhance the stability of the battery at high temperature and high voltage, thereby extending the cycle life of the battery, and also help reduce the internal resistance of the battery at low temperature and improve the low temperature performance of the battery.

[0028] In one embodiment of the present application, the mass ratio of the above-mentioned additive to the first auxiliary agent is 0.3-1:1-12.

[0029] By controlling the mass ratio of the additive to the first auxiliary agent within the above range, the synergistic effect of the additive and the first auxiliary agent is more conducive to enhancing the stability of the SEI film and the embedding / de-embedding efficiency of lithium ions in the electrode material, and is also more conducive to promoting the uniform formation of the SEI film, improving the capacity retention rate of the battery under high temperature storage conditions, and reducing the thickness expansion of the battery. It is also beneficial to reduce capacity attenuation during the battery cycle and improve the cycle stability and safety of the battery.

[0030] In one embodiment of the present application, the electrolyte further includes a second auxiliary agent, and the second auxiliary agent includes C 4 H 6 N 2 and / or LiPO 2 F 2 , C 4 H 6 N 2 The mass of LiPO accounts for 0.5-1.5wt% of the total mass of the electrolyte, and / or LiPO 2 F 2 The mass of the electrolyte accounts for 0.1 to 1 wt% of the total mass of the electrolyte.

[0031] C 4 H 6 N 2 and LiPO 2 F 2 It is beneficial to promote the formation of SEI film, enhance the stability and conductivity of SEI film, and at the same time, LiPO 2 F 2 It is also beneficial to improve the high temperature performance and cycle stability of the battery. 4 H 6 N 2 and LiPO 2 F 2 The content within the above range is beneficial to improving the discharge capacity of the battery at low temperatures, enhancing the cycle stability and storage performance of the battery under high temperature conditions, and is also beneficial to reducing the growth rate of the internal resistance of the battery during the cycle process and extending the service life of the battery.

[0032] In one embodiment of the present application, the above-mentioned organic solvent includes ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate and propyl propionate; wherein the mass ratio of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate and propyl propionate is 10-20:5-15:5-15:5-15:45-60.

[0033] Organic solvents provide the basic electrochemical environment of the electrolyte and are crucial to the performance of the battery, especially affecting the transmission efficiency of lithium ions and the formation of the SEI film. By controlling the combination and proportion of organic solvents within the above range, it is beneficial to improve the conductivity of the electrolyte, reduce the internal loss of the battery during the charge and discharge process, and promote the stable formation of the SEI film, thereby improving the battery's cycle efficiency and high and low temperature working performance, and extending the battery's service life.

[0034] In one embodiment of the present application, the above-mentioned LiPF 6 The mass of the electrolyte accounts for 10-15wt% of the total mass of the electrolyte.

[0035] LiPF 6 As a lithium salt, it is one of the key components in the electrolyte. Its concentration directly affects the conductivity of the electrolyte and the electrochemical performance of the battery, including the conductivity of lithium ions and the cycle stability of the battery. 6 The concentration of LiPF in the above range is beneficial to improve the conductivity of the battery, thereby improving the charge and discharge efficiency of the battery, while reducing the 6 It can reduce the performance degradation and safety problems caused by too high or too low concentration, and improve the overall performance of the battery.

[0036] In one embodiment of the present application, the electrolyte includes, by weight percentage, 0.1-3 wt% of vinyl trimethoxy silane, 0.1-3 wt% of propane sulfonic acid pyridinium salt, 0.1-3 wt% of bis (trimethylsilyl) sulfate, 10-15 wt% of LiPF 6 and an organic solvent; and / or, the electrolyte comprises 0.1 to 3 wt% of vinyl trimethoxy silane, 0.1 to 3 wt% of propane sulfonic acid pyridinium salt, 0.1 to 3 wt% of bis (trimethylsilyl) sulfate, 10 to 15 wt% of LiPF 6 , 0.3-1 wt% of lithium difluorooxalate borate, 1-12 wt% of fluoroethylene carbonate, 0.5-1.5 wt% of C 4 H 6 N 2 , 0.3-1wt% LiPO 2 F 2 and organic solvents.

[0037] Controlling the concentration of each component in the electrolyte within the above range helps each component to exert its optimal electrochemical effect within a specific concentration range. Through the synergistic effect of each component, it is more conducive to achieving an overall improvement in battery performance, thereby helping to improve the battery's cycle efficiency, enhance the battery's thermal stability and safety, extend the battery's service life, and improve the battery's performance under high and low temperature conditions, providing a reliable technical foundation for high energy density and high safety lithium-ion batteries.

[0038] In another typical embodiment of the present application, a lithium-ion battery is provided, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte is the electrolyte described above.

[0039] Lithium-ion batteries including the above-mentioned electrolyte have higher energy density, longer cycle life, better high and low temperature working performance, and higher safety and reliability, and are suitable for applications in various portable electronic products, electric vehicles and energy storage systems.

[0040] The beneficial technical effects of the present application will be described below in combination with specific embodiments and comparative examples.

[0041] Example 1

[0042] A method for preparing a lithium ion battery comprises the following steps performed in sequence:

[0043] Preparation of electrolyte: by mass percentage, in a glove box filled with nitrogen (H 2 O content <0.5ppm), ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate and propyl propionate were mixed in a mass ratio of 15:10:10:10:55 to obtain a mixed solution. Then, 0.30wt% of vinyltrimethoxysilane, 0.30wt% of propanesulfonic acid pyridinium salt, 0.50wt% of bis(trimethylsilyl) sulfate, 15wt% of LiPF were slowly added to the 72.1wt% mixed solution in terms of mass percentage. 6 , 0.50wt% lithium difluorooxalate borate, 10wt% fluoroethylene carbonate, 1.00wt% C 4 H 6 N 2 and 0.30wt% LiPO 2 F 2 After stirring evenly, a lithium ion battery electrolyte is obtained;

[0044] Preparation of positive electrode: The positive electrode active materials LCO, CNT, SP, and PVDF are fully stirred and mixed in a mass ratio of 98:0.6:0.7:0.7, coated on aluminum foil, dried, and cold pressed to obtain a positive electrode sheet;

[0045] Preparation of negative electrode: Silicon-carbon negative electrode material, conductive carbon black, single-walled carbon nanotubes and binder polyacrylic acid are mixed in a mass ratio of 80:9:1:10 and added to solvent deionized water. After mixing evenly, the mixture is coated on copper foil, dried and cold pressed to obtain a negative electrode sheet.

[0046] Example 2

[0047] The difference from Example 1 is that the content of vinyltrimethoxysilane is 0.50wt%, the mass percentage of the mixed solution is 71.9wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0048] Example 3

[0049] The difference from Example 1 is that the content of vinyltrimethoxysilane is 1.0wt%, the mass percentage of the mixed solution is 71.4wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0050] Example 4

[0051] The difference from Example 1 is that the content of vinyltrimethoxysilane is 1.5wt%, the mass percentage of the mixed solution is 70.9wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0052] Example 5

[0053] The difference from Example 1 is that the content of vinyltrimethoxysilane is 2.0wt%, the mass percentage of the mixed solution is 70.4wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0054] Example 6

[0055] The difference from Example 1 is that the content of bis(trimethylsilyl) sulfate is 1.0wt%, the mass percentage of the mixed solution is 71.6wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0056] Example 7

[0057] The difference from Example 1 is that the content of bis(trimethylsilyl) sulfate is 1.5wt%, the mass percentage of the mixed solution is 71.1wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0058] Example 8

[0059] The difference from Example 1 is that the content of bis(trimethylsilyl) sulfate is 2.0wt%, the mass percentage of the mixed solution is 70.6wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0060] Example 9

[0061] The difference from Example 1 is that the content of bis(trimethylsilyl) sulfate is 3.00wt%, the mass percentage of the mixed solution is 69.6wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0062] Example 10

[0063] The difference from Example 1 is that the content of propane sulfonate pyridinium salt is 0.50wt%, the mass percentage of the mixed solution is 71.9wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0064] Embodiment 11

[0065] The difference from Example 1 is that the content of propane sulfonate pyridinium salt is 1.00wt%, the mass percentage of the mixed solution is 71.4wt%, and the remaining components are the same as those in Example 1, and a lithium ion battery is finally obtained.

[0066] Example 12

[0067] The difference from Example 1 is that 2.00wt% of vinyltrimethoxysilane, 1.0wt% of propanesulfonic acid pyridinium salt, and 3.0wt% of bis(trimethylsilyl) sulfate are added to the electrolyte, the mass percentage of the mixed solution is 67.2wt%, and the remaining ingredients are the same as in Example 1, and a lithium ion battery is finally obtained.

[0068] Embodiment 13

[0069] The difference from Example 12 is that 3.00wt% of vinyltrimethoxysilane, 3.00wt% of propanesulfonic acid pyridinium salt, and 3.00wt% of bis(trimethylsilyl) sulfate are added to the electrolyte, the mass percentage of the mixed solution is 64.2wt%, and the remaining ingredients are the same as in Example 1, and a lithium-ion battery is finally obtained.

[0070] Embodiment 14

[0071] The difference from Example 1 is that 3.00 wt% of vinyl trimethoxy silane, 3.00 wt% of propane sulfonic acid pyridinium salt, and 3.00 wt% of bis(trimethylsilyl) sulfate are added to the electrolyte, and fluoroethylene carbonate and C 4 H 6 N 2 , the mass percentage of the mixed solution is 75.2wt%, and a lithium ion battery is finally obtained.

[0072] Embodiment 15

[0073] The difference from Example 13 is that 0.1wt% of vinyltrimethoxysilane, 0.1wt% of propanesulfonic acid pyridinium salt, and 3.00wt% of bis(trimethylsilyl) sulfate are added to the electrolyte, the mass percentage of the mixed solution is 70.0wt%, and a lithium-ion battery is finally obtained.

[0074] Example 16

[0075] The difference from Example 1 is that 0.1 wt % of vinyltrimethoxysilane, 0.1 wt % of propanesulfonic acid pyridinium salt and 0.1 wt % of bis(trimethylsilyl) sulfate are added to the electrolyte, the mass percentage of the mixed solution is 72.9 wt %, and a lithium ion battery is finally obtained.

[0076] Embodiment 17

[0077] The difference from Example 1 is that the electrolyte is prepared as follows: 5.0wt% vinyltrimethoxysilane, 4.0wt% propanesulfonic acid pyridinium salt, 5.0wt% bis(trimethylsilyl) sulfate, the mass percentage of the mixed solution is 59.2wt%, and a lithium ion battery is finally obtained.

[0078] Embodiment 18

[0079] The difference from Example 1 is that the electrolyte is prepared as follows: 0.5wt% of vinyltrimethoxysilane, 0.5wt% of propanesulfonic acid pyridinium salt, 0.5wt% of bis(trimethylsilyl) sulfate, 1.0wt% of lithium difluorooxalatoborate, and 12wt% of fluoroethylene carbonate, and the ratio of the total mass of vinyltrimethoxysilane, propanesulfonic acid pyridinium salt, and bis(trimethylsilyl) sulfate to the total mass of lithium difluorooxalatoborate and fluoroethylene carbonate is 0.75:6.5, and a lithium ion battery is finally obtained.

[0080] Embodiment 19

[0081] The difference from Example 1 is that the electrolyte is prepared as follows: 1.00wt% of vinyltrimethoxysilane, 1.00wt% of propanesulfonic acid pyridinium salt, 1.00wt% of bis(trimethylsilyl) sulfate, 1.00wt% of lithium difluorooxalatoborate, and 12.00wt% of fluoroethylene carbonate, and the ratio of the total mass of vinyltrimethoxysilane, propanesulfonic acid pyridinium salt, and bis(trimethylsilyl) sulfate to the total mass of lithium difluorooxalatoborate and fluoroethylene carbonate is 1.5:6.5, and a lithium ion battery is finally obtained.

[0082] Embodiment 20

[0083] The difference from Example 1 is that the electrolyte is prepared as follows: 4.00wt% of vinyltrimethoxysilane, 4.00wt% of propanesulfonic acid pyridinium salt, 4.00wt% of bis(trimethylsilyl) sulfate, 1.00wt% of lithium difluorooxalatoborate, and 12.00wt% of fluoroethylene carbonate, and the ratio of the total mass of vinyltrimethoxysilane, propanesulfonic acid pyridinium salt, and bis(trimethylsilyl) sulfate to the total mass of lithium difluorooxalatoborate and fluoroethylene carbonate is 6:6.5, and a lithium ion battery is finally obtained.

[0084] Embodiment 21

[0085] The difference from Example 1 is that lithium difluorooxalatoborate and fluoroethylene carbonate are not added to the electrolyte, the mass percentage of the mixed solution is 82.6wt%, and a lithium ion battery is finally obtained.

[0086] Comparative Example 1

[0087] The difference from Example 1 is that the electrolyte is prepared by not adding vinyltrimethoxysilane, propanesulfonic acid pyridinium salt and bis(trimethylsilyl) sulfate, the mass percentage of the mixed solution is 73.2wt%, and the remaining components are the same as in Example 1, and a lithium ion battery is finally obtained.

[0088] Comparative Example 2

[0089] The difference from Example 1 is that the electrolyte is prepared by not adding propane pyridinium sulfonate and bis(trimethylsilyl) sulfate, the mass percentage of the mixed solution is 72.9wt%, and the remaining components are the same as in Example 1, and a lithium ion battery is finally obtained.

[0090] Comparative Example 3

[0091] The difference from Example 1 is that the electrolyte is prepared by not adding vinyltrimethoxysilane and bis(trimethylsilyl) sulfate, the mass percentage of the mixed solution is 72.9wt%, and the remaining components are the same as in Example 1, and finally a lithium ion battery is obtained.

[0092] Comparative Example 4

[0093] The difference from Example 1 is that the electrolyte is prepared by not adding vinyltrimethoxysilane and propanesulfonic acid pyridinium salt, the mass percentage of the mixed solution is 72.7wt%, and the remaining components are the same as in Example 1, and finally a lithium ion battery is obtained.

[0094] Performance Test:

[0095] Cycle performance test: At 25℃ and 45℃, the lithium-ion battery is charged to 4.5V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and left to stand for 10 minutes. Then, the lithium-ion battery is discharged to 3.0V at a constant current rate of 1C, and left to stand for 10 minutes. This is a charge and discharge cycle. The capacity retention rate (%) of the lithium-ion battery after N cycles = (discharge capacity of the Nth cycle / first discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.

[0096] High temperature storage performance test: First, charge and discharge the formed battery at 1.0C to 3.0V at room temperature, and record the initial thickness; charge at 0.2C constant current and constant voltage to 4.5V, and cut off at 0.02C; discharge at 0.2C constant current to 3.0V; as the initial capacity; charge at 0.2C constant current and constant voltage to 4.5V, and cut off at 0.02C; store the battery in a 60℃ constant temperature box for 7 days, then take out the battery, measure the hot thickness (record the hot thickness in the temperature box), leave it for 2h, discharge it at 0.2C constant current to 3.0V, and record it as the residual capacity; charge at 0.2C constant current and constant voltage to 4.5V, and cut off at 0.02C; leave it for 10min; discharge it at 0.2C constant current to 3.0V; record the recovery capacity.

[0097] After storage at 60° C. for 7 days, the thermal thickness expansion rate of the battery = (thermal thickness-initial thickness) / initial thickness*100%.

[0098] After storage at 60°C for 7 days, the battery capacity retention rate = (residual capacity / initial capacity)*100%.

[0099] After storage at 60°C for 7 days, the battery capacity recovery rate = (recovery capacity / initial capacity)*100%.

[0100] The above test results are listed in Table 1.

[0101] Table 1

[0102]

[0103]

[0104] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:

[0105] The present application provides an electrolyte capable of improving the electrical performance of a lithium-ion battery including a silicon negative electrode material by optimizing the combination of additives. Specifically, the vinyl trimethoxysilane additive used in the present application can form an organic polymer containing unsaturated bonds and a cross-polymer network containing Si-O-Si bonds on the surface of the silicon negative electrode, thereby improving the mechanical strength and flexibility of the SEI film. Propane sulfonic acid pyridinium salt and bis (trimethylsilyl) sulfate can form a small amount of sulfur-containing compounds of the positive electrode protective film, and can also be a sulfur-containing compound that is easily decomposed on the positive electrode surface while forming an unstable solid electrolyte passivation film on the negative electrode surface. It can also react with the SEI of the organic polymer containing unsaturated bonds generated by the vinyl trimethoxysilane additive to inhibit the further decomposition of the SEI of the organic polymer, thereby playing a role in modifying the SEI. Through the synergistic effect of the above three additives, a protective layer with a three-dimensional network can be formed on the cathode of the battery, and a cross-linked protective layer is provided respectively to form a SEI with high conductivity and high thermal stability, so that the various performances of the battery are balanced, and the cycle performance and high and low temperature performance of the battery are effectively improved, and the service life of the battery is extended, and the influence of the presence of PS on the body is greatly harmful.

[0106] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes an organic solvent, LiPF6 and an additive, wherein the additive includes vinyltrimethoxysilane, propanesulfonic acid pyridinium salt and bis(trimethylsilyl) sulfate.

2. The electrolyte according to claim 1, characterized in that The mass of the vinyltrimethoxysilane accounts for 0.1 to 5 wt % of the total mass of the electrolyte, the mass of the propanesulfonic acid pyridinium salt accounts for 0.1 to 5 wt % of the total mass of the electrolyte, and the mass of the bis(trimethylsilyl) sulfate accounts for 0.1 to 5 wt % of the total mass of the electrolyte.

3. The electrolyte according to claim 1 or 2, characterized in that The mass ratio of the vinyl trimethoxysilane, the propane sulfonic acid pyridinium salt and the bis(trimethylsilyl) sulfate is 0.1-3:0.1-3:0.1-3.

4. The electrolyte according to any one of claims 1 to 3, characterized in that The electrolyte also includes a first auxiliary agent, which includes lithium difluorooxalatoborate and fluoroethylene carbonate, the mass of the lithium difluorooxalatoborate accounts for 0.3-1wt% of the total mass of the electrolyte, and / or the mass of the fluoroethylene carbonate accounts for 1-12wt% of the total mass of the electrolyte.

5. The electrolyte according to claim 4, characterized in that The mass ratio of the additive to the first auxiliary agent is 0.3-1.5:1-12.

6. The electrolyte according to any one of claims 1 to 5, characterized in that The electrolyte also includes a second auxiliary agent, which includes C4H6N2 and / or LiPO2F2, the mass of C4H6N2 accounts for 0.5-1.5wt% of the total mass of the electrolyte, and / or the mass of LiPO2F2 accounts for 0.1-1.0wt% of the total mass of the electrolyte.

7. The electrolyte according to any one of claims 1 to 6, characterized in that The organic solvent comprises ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate and propyl propionate; wherein the mass ratio of the ethylene carbonate, the propylene carbonate, the diethyl carbonate, the ethyl propionate and the propyl propionate is 10-20:5-15:5-15:5-15:45-60.

8. The electrolyte according to any one of claims 1 to 7, characterized in that The mass of the LiPF6 accounts for 10-15wt% of the total mass of the electrolyte.

9. The electrolyte according to any one of claims 1 to 8, characterized in that In terms of mass percentage, the electrolyte comprises 0.1 to 3 wt % of the vinyl trimethoxy silane, 0.1 to 3 wt % of the propane sulfonic acid pyridinium salt, 0.1 to 3 wt % of the bis(trimethylsilyl) sulfate, 10 to 15 wt % of the LiPF6 and an organic solvent; and / or, the electrolyte comprises 0.1 to 3 wt % of the vinyl trimethoxy silane, 0.1 to 3 wt % of the propane sulfonic acid pyridinium salt, 0.1 to 3 wt % of the bis(trimethylsilyl) sulfate, 10 to 15 wt % of the LiPF6, 0.3 to 1 wt % of lithium difluoro oxalate borate, 1 to 12 wt % of fluoroethylene carbonate, 0.5 to 1.5 wt % of C4H6N2, 0.3 to 1.0 wt % of LiPO2F2 and an organic solvent.

10. A lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The electrolyte solution is the electrolyte solution according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrolyte containing 3-(1-Pyridinio)-1-propanesulfonate and battery using electrolyte

    CN106099183A

  • Application of silicon-based sulfate ester, electrolyte additive, lithium ion battery and electrolyte thereof

    CN109935907A

  • Silicon-based lithium ion battery electrolyte and battery thereof

    CN116632347A

  • High-voltage lithium ion battery electrolyte, preparation method and lithium ion energy storage battery

    CN118738554A

  • Inhibition of electrolyte oxidation in lithium ion batteries with electrolyte additives

    US20110117446A1